Auto-Aggressive Behavior of Adolescents and Socio-Psychological Methods of It’s Prevention - qizi, Axtamova (Jurnal Psikologi, 2025)
This article analyzes the concept of auto-aggressive behavior in adolescents, its contributing factors, and socio-psychological methods of prevention. Auto-aggression encompasses behaviors such as self-harm, low self-esteem, depressive states, and even suicidal tendencies. The development of such behavior can be triggered by factors including family environment, peer relationships, school-related stressors, psychological pressure, and social isolation. The article examines the psychological, social, and biological causes of auto-aggression. It also discusses effective socio-psychological approaches to mitigate this problem, including psychological counseling, stress management techniques, the establishment of social support systems, and preventive measures. Based on the research findings, recommendations aimed at addressing auto-aggressive behavior in adolescents are provided.